APPLICATION OF CIRCULAR ECONOMY IN SHRINKING REGIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Shrinking of rural regions is going on in Eastern and Western European countries. Shrinking phenomena includes Latvia, Lithuania, Estonia and other countries and regions. The shrinking region is considered as untoward and gone territory for economic growth particularly from the perspective of policy makers. Shrinking region requires specific tools for development. The aim of this study is to analyse theoretical options for circular economy development in shrinking regions. The growth economy which requires planning more and more profit, units of goods, jobs etc. is not an adequate strategy for shrinking regions. The desktop approach is applied by analysing research articles on shrinking phenomena and circular economy with aim to explore the potential benefits provided by application of principles of circular economy in shrinking regions. The study also reviews policy planning documents on circular economy and regional development at the European Union level and specifically in Latvia which has lost dramatic proportion of inhabitants in last few decades. The findings of the study show that at first, national policy and EU policy does not accept the phenomena of shrinking regions; second, principles of circular economy are applicable to shrinking regions. There are such challenges as cooperation, philosophy of consumption and values, willingness and availability to pay for services. The study will open a discussion about shrinking rural regions and circular economy from another perspective because until now circular economy is mostly related with the zero waste concept.